The inside battle - Sumrow, Melanie (Yellow Jacket, 2020)
Longing for his father's approval, thirteen-year-old Rebel Mercer follows him inside a racist, anti-government militia group, but when his father plans an attack on an African-American church, Rebel must make the most important decision in his life.